2017
DOI: 10.18203/issn.2454-5929.ijohns20173670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of nasal septum deviation: a study in an urban centre

Abstract: Background: Considerably large nasal septum plays a critical role in the obstruction of the nasal cavity, leading to snoring, and other symptoms, aesthetic appearance of the nose, and increased nasal resistance. This study was performed with an aim to investigate the prevalence of nasal septum deviation in our geographical area. Methods: 446 patients who attended the ENT department in the study period were evaluated for the nasal septum deviation. General demographic details were obtained from all of them. Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…DNS is a very prevalent condition in several parts of the world, with severe symptoms such as nasal obstruction and rhinitis. Although some studies have showed similar results to our findings that DNS is more prevalent in men [ 10 , 11 ], some epidemiology studies reported that women have nearly double the rate of chronic rhinosinusitis (CRS) when compared with men [ 12 , 13 ], whereas other studies found no difference [ 11 , 14 ]. Studies from Saudi Arabia have shown that DNS is more common among males than females [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
“…DNS is a very prevalent condition in several parts of the world, with severe symptoms such as nasal obstruction and rhinitis. Although some studies have showed similar results to our findings that DNS is more prevalent in men [ 10 , 11 ], some epidemiology studies reported that women have nearly double the rate of chronic rhinosinusitis (CRS) when compared with men [ 12 , 13 ], whereas other studies found no difference [ 11 , 14 ]. Studies from Saudi Arabia have shown that DNS is more common among males than females [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our study is in consistent with the study performed in Dehradun, India in which incidence of DNS was three mes more frequent in males 12 than females. Similar results with male predominance have been recorded from India, South Korea, and Saudi [13][14][15] Arabia. Age range of our pa ents was from 6 years to 16 years with the mean age of 12.78 ± 0.35years.…”
Section: Malesupporting
confidence: 88%
“…In our study, the ratio between males and females affected by DNS was 1.1:1, which is similar to the findings seen in the study by Sriprakash. 6 In the studies by Moorthy et al and by Sam et al, the ratio between males and females affected by DNS was 2:1. 7 8 Sam et al mentioned the increased occurrence of trauma among males as one of the reasons for the male preponderance in DNS with trauma being a common etiology for DNS.…”
Section: Discussionmentioning
confidence: 92%